Revisão das seções Acarporophytum, Aristata e Macrospora do gênero Batrachospermum (Rhodophyta, Batrachospermales) - Garcia Filho, Auro Silva [UNESP] (2014)
he three sections of the genus Batrachospermum - Acarposporophytum (with the single species B. brasiliense Necchi), Aristata (B. beraense Kumano, B. cayennense Montagne, B. longiarticulatum Necchi and B. turgidum Kumano) and Macrospora (B. equisetifolium Montagne, B. hypogynum Kumano & Ratnasabapathy and B. macrosporum Montagne) – have been shown to be monophyletic in phylogenetic studies involving at least one member of each section. The following hypotheses were tested: 1) the sections Acarposporophytum, Aristata and Macrospora represent monophyletic groups within the genus Batrachospermum; the sections have been shown to be monophyletic and closely related in previous studies and with the addition of more species and populations this trend will be confirmed; 2) most species currently recognized in each section on the basis of morphological characters will be corroborated by molecular data. This revision of the three sections has the following aims: 1) to infere phylogenetic relationships and the intra-specific limits of variation of the species within and between sections, as well as with the other sections of the genus; the investigation used the morphological diagnostic characters currently applied and three molecular markers - rbcL, the plastidial gene encoding the large sub-unit of RUBISCO; the barcode region of the mithocondrial gene cox1, encoding sub-unit 1 of cythochorme c oxidase; and UPA, plastidial universal plastid amplicon; 2) to carry out a revisional study of the three sections by means of the reevaluation of taxonomic diagnostic characters for species within these groups, in the light of new molecular data. Nineteen new samples were analysed from the southeast, mid-west, north and northeast regions of Brazil, as well as the type specimens of each species and the sequences available in GenBank for each molecular marker. The diagnostic characters for section circumscription and species identification within the sections...